ATBS1-INTERACTING FACTOR 2 Negatively Modulates Pollen Production and Seed Formation in Arabidopsis - Kim, Yoon; Kim, Sun-Ho; Shin, Dong-Min; Kim, Soo-Hwan (Frontiers in Plant Science, 2021)
ATBS1-INTERACTING FACTOR 2 (AIF2) is a non-DNA-binding basic-helix-loop-helix (bHLH) transcription factor. Here, we demonstrate that AIF2 negatively modulates brassinosteroid (BR)-induced, BRASSINAZOLE RESISTANT 1 (BZR1)-mediated pollen and seed formation. AIF2-overexpressing Arabidopsis plants (AIF2ox) showed defective pollen grains and seed production while two AIF2 knockout mutants, aif2-1 and aif2-1/aif4-1, displayed opposite phenotypes. Genes encoding BZR1-regulated positive factors of seed size determination (SHB1, IKU1, MINI3) were suppressed in AIF2ox and genes for negative factors (AP2 and ARF2) were enhanced. Surprisingly, BZR1-regulated pollen genes such as SPL, MS1, and TDF1 were aberrantly up-regulated in AIF2ox plants. This stage-independent abnormal expression may lead to a retarded and defective progression of microsporogenesis, producing abnormal tetrad microspores and pollen grains with less-effective pollen tube germination. Auxin plays important roles in proper development of flower and seeds: genes for auxin biosynthesis such as TCPs and YUCCAs as well as for positive auxin signalling such as ARFs were suppressed in AIF2ox flowers. Moreover, lipid biosynthesis- and sucrose transport-related genes were repressed, resulting in impaired starch accumulation. Contrarily, sucrose and BR repressed ectopic accumulation of AIF2, thereby increasing silique length and the number of seeds. Taken together, we propose that AIF2 is negatively involved in pollen development and seed formation, and that sucrose- and BR-induced repression of AIF2 positively promotes pollen production and seed formation in Arabidopsis.